Perda de visão como forma de apresentação de recidiva de carcinoma da mama - Sousa, Ana E. (1994)
We presenta case of a patient in whom thefirst manifestation of breast carcinoma recurrence ten years after the initial diagnosis was a loss of vision as a result of a choroidal metástase. A clear therapeutic response to tamoxifen was seen. Choroidal metástases are rare in clinicai onco logical practice and are considered exceptional as aform of presentation of a recurrence of breast carcinoma. Radiotherapy is the usual paliative therapy. This unusual response to tamoxifen is emphasized in view of the absence of simi lar reports in the literature.